Isolation and Characterization of Environmental Extended Spectrum β-Lactamase-Producing Escherichia coli and Klebsiella pneumoniae from Ouagadougou, Burkina Faso - Alix Bénédicte Kagambèga; René Dembélé; Oumar Traoré; Abdoul Aziz Wane; Alassane Halawen Mohamed; Hiliassa Coulibaly; Cheikh Fall; Léa Bientz; Fatima M'Zali; Laure Mayonnove; Nicolas Barro; Véronique Dubois; et al. (MDPI AG, 2024)
Antimicrobial resistance (AMR) is a global public health threat. Quality data are needed to address the rise of multidrug-resistant clones, particularly in sub-Saharan Africa. In this study, we analysed the prevalence, antimicrobial resistance profile, and presence of genes encoding extended-spectrum β-lactamase-producing Escherichia coli (ESBL-Ec) and Klebsiella pneumoniae (ESBL-Kp) in environmental samples from Ouagadougou, Burkina Faso. Of 264 samples collected, 95 (36%) and 74 (28%) contained ESBL-Kp and ESBL-Ec, respectively. ESBL-Kp was more prevalent in runoff water and in treated and untreated wastewater, while ESBL-Ec was more prevalent in manure. Interestingly, wastewater treatment did not significantly reduce the recovery of ESBL bacteria. As expected, resistance to third- and fourth-generation cephalosporins was predominant, and rare for second generation cefoxitin. Interestingly, all the isolates from treated wastewater were susceptible to ampicillin and piperacillin, while all the other clones were resistant to these antibiotics. Regarding the ESBL-encoding genes, the blaCTX-M family was the most abundant, with the blaCTX-M1 subfamily being the most prevalent. Carriage of combinations of ESBL genes was common, with the majority of the isolates harbouring 2-4 different genes. This study highlights the need for active surveillance to manage the risk of exposure to ESBL bacteria in Burkina Faso.